Treatments for Ocular Diseases in Pregnancy and Breastfeeding: A Narrative Review - Giuseppe Demarinis; Filippo Tatti; Andrea Taloni; Antonio Valentino Giugliano; Jesse Panthagani; James Myerscough; Enrico Peiretti; Giuseppe Giannaccare (MDPI AG, 2023)
Pregnancy is a medical condition in which the physiological changes in the maternal body and the potential impact on the developing fetus require a cautious approach in terms of drug administration. Individual treatment, a thorough assessment of the extent of the disease, and a broad knowledge of the therapeutic options and different routes of administration of ophthalmic drugs are essential to ensure the best possible results while minimizing risks. Although there are currently several routes of administration of drugs for the treatment of eye diseases, even with topical administration, there is a certain amount of systemic absorption that must be taken into account. Despite continuous developments and advances in ophthalmic drugs, no updated data are available on their safety profile in these contexts. The purpose of this review is both to summarize the current information on the safety of ophthalmic treatments during pregnancy and lactation and to provide a practical guide to the ophthalmologist for the treatment of eye diseases while minimizing harm to the developing fetus and addressing maternal health needs.